Realizing SDGs in Indonesia Through Productive Waqf - Hadyantari, Faizatu Almas (UI Scholars Hub, 2022)
Waqf is a form of Islamic social financial instrument that has sustainability benefits. Efforts to produce waqf assets aim to increase their use to create an even distribution in all aspects. This is in line with the Sustainable Development Goals (SDGs), namely maintaining sustainable improvement in the economic welfare of the community, maintaining the sustainability of community social life, and maintaining environmental quality. the pillars of development are the pillars of social development, the pillars of economic development, the pillars of environmental development, and the pillars of governance and law. The research method used is a qualitative study of literature with descriptive analysis techniques. This article wants to show that the optimization of productive waqf is an alternative to realizing the Sustainable Development Goals in Indonesia. This is done through its role in managing waqf assets and developing the utilization of waqf results through economic empowerment. It is hoped that these efforts can participate in solving economic problems such as unemployment, socio-economic disparities, community welfare, and the environment.